PERTUMBUHAN DAN HASIL BEBERAPA VARIETAS BAWANG MERAH (Allium ascalonicum L) PADA TANAH ALUVIAL AKIBAT PEMBERIAN BERBAGAI DOSIS PUPUK NPK - Mehran Mehran; Ely Kesumawaty; Sufardi Sufardi (Program Studi Agroteknologi, Fakultas Pertanian, Universitas Syiah Kuala, 2016)
Alluvial soil had higher levels of organic matter and N-total were classified as very low that use of NPK fertilizer with an adequate dose is expected to improve the physical and chemical properties of soil and increase the yield of onion. Red onion (Allium ascalonicum L) is one of the horticultural crops that can be grown in alluvial soil. The research aims to determine the effect on the optimal dose of NPK fertilizer and productivity of onion on Alluvial soil. Field experiments conducted in Gardens Visitor Plot Institute for Agricultural Technology (BPTP) Banda Aceh, in February - Mai 2015. The experimental design used was a randomized block design (RBD) factorial 4 x 4 treatment and 3 replications. If there is highly significant or significant difference will be continued primarily to test BNT0,05%. The composition of the treatment is Pikatan (V1), Mentes (V2), Pancasona (V3) and Trisula (V4) and NPK Control, 200 kg h-1, 400 kg h-1 and 600 kg h-1. Results of bulb wet weight h-1 = 9,50 tonnes h-1) and dry tuber weight (7,33 tonnes h-1), but no significant effect on plant height and number of tillers 2 MST. The implications of this study tht the use of varieties Pancasona and NPK fertilizer dose of 600 kg h-1 can be applied to the alluvial soil.